A Transcriptional and Metabolic Framework for Secondary Wall Formation in Arabidopsis. Issue 2 (26th August 2016) - Li, Zheng; Omranian, Nooshin; Neumetzler, Lutz; Wang, Ting; Herter, Thomas; Usadel, Bjoern; Demura, Taku; Giavalisco, Patrick; Nikoloski, Zoran; Persson, Staffan
Abstract : Network analyses reveal metabolic pathways associated with secondary cell wall synthesis and provide a framework for a better understanding of plant biomass formation. Abstract: Plant cell walls are essential for plant growth and development. The cell walls are traditionally divided into primary walls, which surround growing cells, and secondary walls, which provide structural support to certain cell types and promote their functions. While much information is available about the enzymes and components that contribute to the production of these two types of walls, much less is known about the transition from primary to secondary wall synthesis. To address this question, we made use of a transcription factor system in Arabidopsis ( Arabidopsis thaliana ) in which an overexpressed master secondary wall-inducing transcription factor, VASCULAR-RELATED NAC DOMAIN PROTEIN7, can be redirected into the nucleus by the addition of dexamethasone. We established the time frame during which primary wall synthesis changed into secondary wall production in dexamethasone-treated seedlings and measured transcript and metabolite abundance at eight time points after induction. Using cluster- and network-based analyses, we integrated the data sets to explore coordination between transcripts, metabolites, and the combination of the two across the time points. We provide the raw data as well as a range of network-based analyses. These data reveal links between hormone signaling and metabolic processes during the formation of secondary walls and provide a framework toward a deeper understanding of how primary walls transition into secondary walls.